The Competitive Advantage between Intellectual Capital and Financial Performance of Banking Sector in ASEAN - Rochmadhona, Bella Nursyarifa; Suganda, Tarsisius Renald; Cahyadi, Sendy (Jurnal Keuangan dan Perbankan, 2018)
This research aims to examine the mediating effect of competitive advantage in the relationship between intellectual capital and financial performance of the banking sector in five ASEAN countries. Furthermore, this research analyzes the differentiation level of intellectual capital using its components namely human capital, structural capital, and relational capital measured by Extended VAIC Plus (E-VAIC+). This research using partial least square method to test the mediation effect and ANOVA to test the differentiation level of intellectual capital on the banking sector in five ASEAN countries. The results show intellectual capital has a positive effect to financial performance and competitive advantage, competitive advantage has a positive effect to financial performance, and there is a different level of intellectual capital in Indonesia, Laos, Vietnam, Philippines, and Thailand. These findings support the resource-based theory which asserts that a unique set of resources that are owned and controlled can make the company have sustainable superior performance. These resources can be derived from the intellectual capital component that is exploited in such a way as a competitive advantage.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i2.2060